2016
DOI: 10.3390/cells5040044
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Induced Pluripotent Stem Cells (iPSCs) for Treating Age-Related Macular Degeneration (AMD)

Abstract: The field of stem cell biology has rapidly evolved in the last few decades. In the area of regenerative medicine, clinical applications using stem cells hold the potential to be a powerful tool in the treatment of a wide variety of diseases, in particular, disorders of the eye. Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) are promising technologies that can potentially provide an unlimited source of cells for cell replacement therapy in the treatment of retinal degenerative disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…Although this procedure did not attempt to restore the vision of the patient, since this is very unlikely, it nevertheless provided an opportunity to monitor side effects, immunogenicity or cancer growth in a human patient. To date it constitutes the first clinical trial on a practical aspect of the iPSCs with a positive outcome, illustrating current hopes in regenerative therapies as evidenced by several other ongoing clinical trials for ARMD treatments using iPSCs or ESCs (118,119). Moreover, new prospects for the treatment of hypertension using iPSCs have recently been described (120).…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 85%
“…Although this procedure did not attempt to restore the vision of the patient, since this is very unlikely, it nevertheless provided an opportunity to monitor side effects, immunogenicity or cancer growth in a human patient. To date it constitutes the first clinical trial on a practical aspect of the iPSCs with a positive outcome, illustrating current hopes in regenerative therapies as evidenced by several other ongoing clinical trials for ARMD treatments using iPSCs or ESCs (118,119). Moreover, new prospects for the treatment of hypertension using iPSCs have recently been described (120).…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 85%
“…Takahashi had claimed to stop the degeneration process and the patient experienced an improvement in vision [126]. The trial was halted due to unexplained mutations observed by Yamanaka in the transplanted RPE and the patients' iPS [126,127]. This trial proved that several safety assays need to be established to validate preclinical studies before they are safe to begin future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, animal studies have been translated into clinical trials of this cell replacement approach, but, so far, with inconclusive results. 3 Additionally, ESC use is fraught with ethical concerns. iPSCs might form teratomas due to incomplete differentiation or spontaneously mutate, which has caused a temporary halt of one clinical trial in Japan.…”
Section: A Different Approach Involves Rpe Derived From Embryonic Stementioning
confidence: 99%
“…Anti-VEGF therapies are fairly efficient at counteracting this neovascularization and are currently the mainstream treatment for wet AMD. 3 However, no treatment has been effective so far for the more common dry form.…”
mentioning
confidence: 99%